CLEAR thrombectomy score: an index to estimate the probability of good functional outcome with or without endovascular treatment in the late window for anterior circulation occlusion - Siegler, James E.; Koneru, Manisha; Qureshi, Muhammad M.; Doheim, Mohamed; Nogueira, Raul G.; Martinez‐Majander, Nicolas; Nagel, Simon; Penckofer, Mary; Demeestere, Jelle; Puetz, Volker; Ribo, Marc; Abdalkader, Mohamad; et al. (Journal of the American Heart Association, 2024)
Background - With the expanding eligibility for endovascular therapy (EVT) of patients presenting in the late window (6-24 hours after last known well), we aimed to derive a score to predict favorable outcomes associated with EVT versus best medical management. - Methods and Results - A multinational observational cohort of patients from the CLEAR (Computed Tomography for Late Endovascular Reperfusion) study with proximal intracranial occlusion (2014-2022) was queried (n=58 sites). Logistic regression analyses were used to derive a 9‐point score for predicting good functional outcome (modified Rankin Scale score 0-2 or return to premorbid modified Rankin Scale score) at 90 days, with sensitivity analyses for prespecified subgroups conducted using bootstrapped random forest regressions. Secondary outcomes included 90‐day functional independence (modified Rankin Scale score 0-2), poor outcome (modified Rankin Scale score 5-6), and 90‐day survival. The score was externally validated with a single‐center cohort (2014-2023). Of the 3231 included patients (n=2499 EVT), a 9‐point score included age, early computed tomography ischemic changes, and stroke severity, with higher points indicating a higher probability of a good functional outcome. The areas under the curve for the primary outcome among EVT and best medical management subgroups were 0.72 (95% CI, 0.70-0.74) and 0.87 (95% CI, 0.84-0.90), respectively, with similar performance in the external validation cohort (area under the curve, 0.71 [95% CI, 0.66-0.76]). There was a significant interaction between the score and EVT for good functional outcome, functional independence, and poor outcome (all Pinteraction<0.001), with greater benefit favoring patients with lower and midrange scores. - Conclusions - This score is a pragmatic tool that can estimate the probability of a good outcome with EVT in the late window. - Registration - URL: https://www.Clinicaltrials.gov; Unique identifier: NCT04096248.